2014
DOI: 10.1002/2014rs005409
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of HF system performance for propagation through disturbed ionospheres measured using low-Earth-orbit satellite radio beacon tomography

Abstract: The CERTO radio beacon on the C/NOFS satellite sends VHF/UHF radio signals at 150 and 400 MHz to provide measurements of integrated electron density or Total Electron Content (TEC) by an east-west chain of ground receivers in Peru. Computerized Ionospheric Tomography (CIT) is used to convert the TEC data into two-dimensional images of electron densities with maximum 5 × 5 km resolution in Longitude-Altitude space. These images are updated every 95 min as the C/NOFS satellite passes over the receiver network in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…As of now, such experiments can be carried out, e.g., using the ePOP payload onboard the Canadian CASSIOPE satellite [ Siefring et al , ]. Similar experiments with the ePOP satellite have been proposed by Bernhardt et al [] using the coherent electromagnetic radio tomography beacon and the radio receiver instrument on the satellite to detect the effects natural irregularities on HF radio transmissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As of now, such experiments can be carried out, e.g., using the ePOP payload onboard the Canadian CASSIOPE satellite [ Siefring et al , ]. Similar experiments with the ePOP satellite have been proposed by Bernhardt et al [] using the coherent electromagnetic radio tomography beacon and the radio receiver instrument on the satellite to detect the effects natural irregularities on HF radio transmissions.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies, e.g., for the region of the northern crest of equatorial anomaly are presented in Kryukovsky and Kiryanova []. The HF ray‐tracing technique has also be employed for natural irregularities at the equator measured with satellite beacon tomography [ Bernhardt et al , ].…”
Section: Experimental Setup and Data Processingmentioning
confidence: 99%
“…For these models to be sufficiently accurate, two conditions must be satisfied. First, the spatial resolution must be less than the Fresnel diffraction scale (Bernhardt et al, 2014; Rino, 2011). Second, any material objects in the spatial domain of interest must be larger than the wavelength of the incident wave (Smith et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Many numerical methods have been used to study the backscattering process and better map the location of irregularities from observed data (Bernhardt et al, 2014; Cervera & Harris, 2014; Chisham et al, 2008; Greenwald et al, 1995; Liu et al, 2012). The majority of these models are based on ray tracing, an approach that treats the HF waves as rays and only tracks the primary direction of energy flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation